2011
DOI: 10.1007/s10549-011-1829-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinician awareness and knowledge of breast cancer-related lymphedema in a large, integrated health care delivery setting

Abstract: Breast cancer survivors have reported dissatisfaction regarding their education on risk of breast cancer-related lymphedema (BCRL) from clinicians. We describe clinician knowledge and treatment referral of patients with BCRL among active oncologists, surgeons, and primary care physicians in the Kaiser Permanente Northern California Medical Care Program. A total of 887 oncologists, surgeons, and primary care clinicians completed a 10-minute web survey from May 2, 2010 to December 31, 2010 on BCRL knowledge, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…Further, health care providers (e.g., surgeons, oncologists, and nurses) play a vital role in cancer rehabilitation through referring patients to see an OT lymphedema specialist. Tam and colleagues [14] found that 100 % of oncologists, 79 % of surgeons, and 36 % of primary care clinicians in their study reported having ever made a referral for breast cancer-related lymphedema.…”
Section: Introductionmentioning
confidence: 94%
“…Further, health care providers (e.g., surgeons, oncologists, and nurses) play a vital role in cancer rehabilitation through referring patients to see an OT lymphedema specialist. Tam and colleagues [14] found that 100 % of oncologists, 79 % of surgeons, and 36 % of primary care clinicians in their study reported having ever made a referral for breast cancer-related lymphedema.…”
Section: Introductionmentioning
confidence: 94%
“…Foreign substances such as bacteria and toxins are filtered and destroyed in the nodes. The lymph vessels finally open into large ducts-the thoracic duct and right lymphatic duct-and then drain into the neck veins [1][2][3][4].…”
Section: Description Incidence and Stages Of Lementioning
confidence: 99%
“…The debilitating pain, anguish, suffering, and disfiguring swelling of LE can cause physical and emotional distress. Women who develop LE face a lifetime of treatment [2][3][4][5]. BCRL symptoms can develop any time after breast cancer treatment.…”
Section: Description Incidence and Stages Of Lementioning
confidence: 99%
See 2 more Smart Citations